Effects of BSF on Podocyte Apoptosis via Regulating the ROS-Mediated PI3K/AKT Pathway in DN - Fang-qiang Cui; Yue-Fen Wang; Yan-bin Gao; Yuan Meng; Zhen Cai; Cun Shen; Zhi-qiang Liu; Xin-can Jiang; Wen-jing Zhao (Journal of Diabetes Research)
Diabetic nephropathy (DN) is the leading cause of end-stage renal disease (ESRD). The ROS-mediated PI3K/AKT pathway plays a key role in podocyte apoptosis and DN progression. Our previous study demonstrated that Baoshenfang (BSF) can decrease proteinuria and attenuate podocyte injury. However, the effects of BSF on podocyte apoptosis induced by the ROS-mediated PI3K/AKT pathway remain unclear. Herein, in vivo and in vitro studies have been performed. In our in vivo study, BSF significantly decreased 24-h urinary protein, serum creatinine, and blood urea nitrogen levels in DN mice. Meanwhile, BSF significantly inhibited oxidative stress and podocyte apoptosis in our in vivo and in vitro studies. Moreover, BSF significantly decreased the inhibition of the PI3K/AKT pathway induced by HG in DN. More importantly, the effects of BSF on podocyte apoptosis were reversed by PI3K siRNA transfection. In conclusion, BSF can decrease proteinuria and podocyte apoptosis in DN, in part through regulating the ROS-mediated PI3K/AKT pathway.